2019
DOI: 10.1002/ange.201912475
|View full text |Cite
|
Sign up to set email alerts
|

Freeing the Polarons to Facilitate Charge Transport in BiVO4 from Oxygen Vacancies with an Oxidative 2D Precursor

Abstract: The BiVO4 photoelectrochemical (PEC) electrode in tandem with a photovoltaic (PV) cell has shown great potential to become a compact and cost‐efficient device for solar hydrogen generation. However, the PEC part is still facing problems such as the poor charge transport efficiency owing to the drag of oxygen vacancy bound polarons. In the present work, to effectively suppress oxygen vacancy formation, a new route has been developed to synthesize BiVO4 photoanodes by using a highly oxidative two‐dimensional (2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…In this concern, Qiu et al established an internal oxidant route for the synthesis of nanoporous BiVO 4 photoanode by which polaron hopping obstacles are minimized causing a sudden increase in electron mobility. [107] The O v fix the polaron and hinder its transport through BiVO 4 , which resulted in photocurrent density of 4.8 mA cm −2 at 1.23 V RHE and the η sep of ≈91%.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…In this concern, Qiu et al established an internal oxidant route for the synthesis of nanoporous BiVO 4 photoanode by which polaron hopping obstacles are minimized causing a sudden increase in electron mobility. [107] The O v fix the polaron and hinder its transport through BiVO 4 , which resulted in photocurrent density of 4.8 mA cm −2 at 1.23 V RHE and the η sep of ≈91%.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…As an example, a recent study showed the suppression of the formation of oxygen vacancies leading to a higher PEC performance due to an increase of the conductivity as a consequence of the release of bound polarons. 61 The synthesis of black BiVO 4 has been reported, as a new black material. 63 Herein, nanosized black BiVO 4 colloids were prepared by laser irradiation of bulk particles.…”
Section: Bismuth Vanadate Bivomentioning
confidence: 99%
“…This in turn results in an increase in the amount of oxygen vacancies in BiVO 4 samples to maintain charge neutrality. , The incomplete oxidation of vanadium can be unintentional, but it is also a common strategy for improving the efficiency of photoanodes based on BiVO 4 . , , However, the role of oxygen vacancies in BiVO 4 is not entirely without controversy. It has been reported both that they enhance and diminish the charge transfer properties of the material.…”
Section: Introductionmentioning
confidence: 99%